Ilmu Kedokteran Forensik Sebagai Ilmu Bantu Dalam Penegakan Hukum Pidana Di Indonesia - Tia Ningsih (Universitas Widya Gama Malang, 2022)
The purpose of writing this article is to understand and identify the forms of the role of forensic medicine in assisting criminal law enforcement and to find out the legal consequences for forensic doctors who refuse to give their statements as expert witnesses in criminal justice. This study uses a normative juridical legal research method using a statue approach and a conceptual approach. The results of this study are forensic medical science in criminal law enforcement, which acts as an auxiliary science that can reveal facts about the existence or absence of criminal events, to reveal the process of criminal acts and their consequences, to determine the time of the crime, to find out the truth of how the crime occurred, the ways and signs that occur in a criminal event, as well as to reveal the identity of the perpetrator of the crime and the identity of the victim in the case of a mysterious corpse, in which the disclosure of these facts is carried out by a forensic doctor in the form of expert testimony that serves as legal evidence in criminal justice so that it can be considered by judges to decide and try a criminal case. If the authorized law enforcer requests assistance from a forensic doctor to provide his testimony as an expert witness, either orally (directly in court) or in writing (in the form of a Visum et Repertum), the forensic doctor is obliged to do so If the forensic doctor refuses to give his testimony as an expert witness in criminal justice, he can be subject to Article 224 of the Criminal Code with a maximum imprisonment of nine months (for criminal cases) or a maximum imprisonment of six months (for cases other than criminal). Article 522 of the Criminal Code with a maximum fine of nine hundred thousand rupiah.